Longitudinal epidemiology of human coronavirus OC43 in Yamagata, Japan, 2010–2017: Two groups based on spike gene appear one after another. Issue 2 (13th August 2020) - Komabayashi, Kenichi; Matoba, Yohei; Tanaka, Shizuka; Seto, Junji; Aoki, Yoko; Ikeda, Tatsuya; Shimotai, Yoshitaka; Matsuzaki, Yoko; Itagaki, Tsutomu; Mizuta, Katsumi
Abstract: Human coronavirus OC43 (HCoV‐OC43) is divided into genotypes A to H based on genetic recombination including the spike ( S ) gene. To investigate the longitudinal transition of the phylogenetic feature of the HCoV‐OC43 S gene in a community, phylogenetic analysis of the S1 region of the  S gene was conducted using 208 strains detected in Yamagata during 2010 to 2017 with reference strains of the genotype. The S1 sequences were divisible into four groups: A to D. All Yamagata strains belonged to either group B or group D. In group B, 46 (90.2%) out of 51 Yamagata strains were clustered with those of genotype E reference strains (cluster E). In group D, 28 (17.8%) and 122 (77.7%) out of 157 Yamagata strains were clustered, respectively, with genotype F and genotype G reference strains. In cluster G, 28 strains formed a distinct cluster. Monthly distributions of HCoV‐OC43 in Yamagata in 2010 to 2017 revealed that group B and group D appeared one after another. In group B, the cluster E strains were prevalent recurrently. In conclusion, epidemics of HCoV‐OC43 in Yamagata, Japan might be attributable to two genetically different groups: group B showed a recurrent epidemic of strains belonging to a single phylogenetic cluster and group D showed epidemic strains belonging to multiple clusters. Highlights: Longitudinal transition of the phylogenetic feature of the HCoV‐OC43 spike gene in a community. Epidemics of HCoV‐OC43 in Yamagata, Japan might be attributable to two genetically different groups.